2018
DOI: 10.1371/journal.pone.0205077
|View full text |Cite
|
Sign up to set email alerts
|

Smoking-induced control of miR-133a-3p alters the expression of EGFR and HuR in HPV-infected oropharyngeal cancer

Abstract: PurposeHuman papillomavirus (HPV) infected oropharyngeal squamous cell carcinoma (OPSCC) patients have a better prognosis compared to HPV(-) counterparts. However, a subset of HPV(+) patients with a smoking history fail to respond to the standard of care treatments such as radiation and chemotherapy. To understand the underlying mechanism driving HPV(+) OPSCC patient resistance to treatment and recurrence, we sought to identify and characterize the differentially expressed miRNAs and their target genes in HPV(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 41 publications
(46 reference statements)
0
17
0
2
Order By: Relevance
“…Cigarette smoke has been suggested to contribute to HPV + HNC progression by altering the expression pattern of miRNA in epithelial cells especially miRNA-133a-3p [49,50]; miRNA-133a-3p inhibits proliferation/invasion of HNC [51] and acts as a tumor suppressor miRNA [52]. A recent study demonstrated that smoking or cigarette smoke extract, down-regulates the expression levels of miRNA-133a-3p [50]; down-regulation of miRNA-133a-3p is associated with an increase in the expression levels of epithelial growth factor receptor (EGFR) and Hu-antigen R (involved in post-transcriptional regulation), which contribute to tumor growth [50,53]. Thus, smoking contributes to the progression of HPV + HNC by upregulating the expression of EGFR and HuR.…”
Section: Influence Of Smoking In Hpv + Hncmentioning
confidence: 99%
“…Cigarette smoke has been suggested to contribute to HPV + HNC progression by altering the expression pattern of miRNA in epithelial cells especially miRNA-133a-3p [49,50]; miRNA-133a-3p inhibits proliferation/invasion of HNC [51] and acts as a tumor suppressor miRNA [52]. A recent study demonstrated that smoking or cigarette smoke extract, down-regulates the expression levels of miRNA-133a-3p [50]; down-regulation of miRNA-133a-3p is associated with an increase in the expression levels of epithelial growth factor receptor (EGFR) and Hu-antigen R (involved in post-transcriptional regulation), which contribute to tumor growth [50,53]. Thus, smoking contributes to the progression of HPV + HNC by upregulating the expression of EGFR and HuR.…”
Section: Influence Of Smoking In Hpv + Hncmentioning
confidence: 99%
“…Among the dysregulated hypoxiaassociated microRNAs, miR-133a-3 was considered to be a novel prognosis biomarker for hypoxic tumors with elevated risk for distant metastasis [100]. MiR-133a-3p dysregulation was also found in smoking-induced HPV (+) oropharyngeal cancer patients [101]. Taken together, the dysregulation of miR-133a occurs at the early stage of tumorigensis, and low expression of miR-133a frequently indicates poor prognosis, which is consistent with its tumorsuppressive role in cancer development and progression.…”
Section: Mir-133a As a Potential Biomarkermentioning
confidence: 99%
“…There is recent hypothesis about the role of HPV in these cancers [32]. The most plausible cause of correlation between cervical and lung or bladder cancers is the common risk factor of smoking [32][33][34].…”
Section: Lung and Bladdermentioning
confidence: 99%